The International Labour Organization: 100 Years of Global Social Policy - Maul, Daniel (De Gruyter, 2019)
This book is the first comprehensive account of the International Labour Organization's 100-year history. At its heart is the concept of global social policy, which encompasses not only social policy in its national and international dimensions, but also development policy, world trade, international migration and human rights. The book focuses on the ILO's roles as a key player in debates on poverty, social justice, wealth distribution and social mobility subjects and as a global forum for addressing these issues. The study puts in perspective the manifold ways in which the ILO has helped structure these debates and has made – through its standard-setting, technical cooperation and myriad other activities – practical contributions to the world of work and to global social policy.